-6
n = -6
12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n
2n/3 = 4 2n = 3*4 2n = 12 n = 6 :)
A equals 4 because 4 plus 6 is 10 or 10 minus 6 is 4.
2n plus 7 equals 19 2n equals 12 n equals 6
the answer is 0
Given that 2n = 6 + n, subtract n from each side and n = 6
6+5n=2n-9Isolate the variable by subtracting 2n and 6 from both sides.5n-2n=-9-63n=-15n=-5
-6
Well, if 6 equals 1 plus five, the 2n you put in the middle must be nothing. Think. n=0 Sorry If it's not right
Solve for n. 6 = 1 - 2n + 5 6 = 6 - 2n 2n = 0 n = 0 Check it. 6 = 1 - 0 + 5 It checks.
6=(1-2n)+5 6-5=(1-2n)+5-5 1=1-2n 1-1=1-1-2n 0=-2n 0/-2=-2n/-2 0=n
n = -6
12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n
2n/3 = 4 2n = 3*4 2n = 12 n = 6 :)
2(2n + 5) = 12 2n + 5 = 6 2n = 1 n = 1/2